2018
DOI: 10.1101/393892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized cross-linking mass spectrometry for in situ interaction proteomics

Abstract: Recent development of mass spectrometer cleavable protein cross-linkers and algorithms for their spectral identification now permits large-scale cross-linking mass spectrometry (XL-MS).Here, we optimized the use of cleavable disuccinimidyl sulfoxide (DSSO) cross-linker for labeling native protein complexes in live human cells. We applied a generalized linear mixture model to calibrate cross-link peptide-spectra matching (CSM) scores to control the sensitivity and specificity of large-scale XL-MS. Using specifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…S1E). This is consistent with the accuracy of CL-MS observed in prior studies (26), and indicates high confidence in detected interactions.…”
Section: Resultssupporting
confidence: 91%
“…S1E). This is consistent with the accuracy of CL-MS observed in prior studies (26), and indicates high confidence in detected interactions.…”
Section: Resultssupporting
confidence: 91%
“…For example, a lower value of 20 could be used for the stHCD data that gives rise to 183 correct crosslinks (11 more than with a score cut-off of 40) and 8 incorrect, resulting in a calculated FDR of 4.1%. A similar approach was taken by Ser et al 5 by spiking crosslinked BSA peptides into non-crosslinked proteome background peptides to calculated score filters that removed 99% and 90% of non-BSA crosslinks to determine FDR cut-offs for 1% and 10% FDR, respectively. The data included in the present publication could be even more useful for a systematic optimisation of search and validation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Initial applications of these techniques were limited to small proteins and protein complexes. More recently, due to major methodological and technological developments, XL-MS has been applied to living cells to investigate protein interactions and topological structures at the proteome-wide level [5][6][7][8] .…”
mentioning
confidence: 99%
“…BioID-based proximity biotinylation of proteins occurs on lysine residues, which can inhibit efficient digestion with trypsin (39,40). Previous studies of cross-linking MS using lysine-reactive cross-linkers (e.g., DSSO) have shown that sequential digestion with Lys-C or other non-lysine-specific proteases (e.g., Glu-C) followed by trypsin increases the coverage of identified cross-linked peptides (41,42).…”
Section: Sequential Digestion With Different Proteasesmentioning
confidence: 99%